Acute abdominal compartment syndrome: current diagnostic and therapeutic options - Hecker, Andreas; Hecker, Birgit; Hecker, Matthias; Riedel, J. G.; Weigand, Markus A.; Padberg, Winfried (Langenbeck's archives of surgery, 2016)
If untreated, the abdominal compartment syndrome (ACS) has a mortality of nearly 100 %. Thus, its early recognition is of major importance for daily rounds on surgical intensive care units. Intraabdominal hypertension (IAH) is a poorly recognized entity, which occurs if intraabdominal pressure arises >12 mmHg. Measurement of the intravesical pressure is the gold standard to diagnose IAH, which can be detected in about one fourth of surgical intensive care patients.
Published online: 30 October 2015
Gesehen am 07.05.2020